Réponses

  • Utilisateur Brainly
2014-04-16T15:54:01+02:00
Résoudre les équations : 

a) 5 + 6x = - x - 9
6x + x  = - 9 + 5
7x = - 4
x = -4/7

b) 11x + 3 = 8x + 7
11x - 8x = 7 - 3
3x = 4
x = 4/3

c) 5,5 + 1,5 = 9x + 6
5,5 + 1,5 + 6 = 9x
13 = 9x
x = 13/9

d) 7 - 3,3x = 2x - 9,7
7 + 9,7 = 2x + 3,3x
16,7 = 5,3x
x = 16,7/5,3

e) 5,1 - x = - 8x + 1,7
- x + 8x = 1,7 - 5,1
7x = - 3,4
x = -3.4/7

2014-04-16T16:05:07+02:00
A) 5+6x= -x-9
    5+6x-5+x= -x-9-5+x
    7x/7 = -14/7
     x= -2

b) 11x +3 = 8x +7
     11x+3-3-8x= 8x +7 -3 -8x
      3x/3=4/3
      x= 4/3

c) 5,5 +1,5= 9x+6
    5,5 +1,5-6= 9x +6-6
    1/9=9x/9
     x= 1/9

d) 7-3,3x= 2x-9,7
   7-3,3x-7-2x= 2x-9,7-7-2x
   -5,3x/-5,3= -16,7/-5,3
    x= 3,34

e) 5,1-x= -8x +1,7
    5,1 -x -5,1 +8x= -8x +1,7 -5,1 +8x
    7x/7= -3,4/7
     x= -17/35